Relationship between Social Networking Sites and Observational Learning among Senior Secondary School Students in Mbaitoli Local Government Area, Imo State, Nigeria - Achilike, Beatrice Adanna; Mgboro, Chibueze Utum; Patrick, Agbasiere, Emmanuel (European Scientific Journal, ESJ, 2018)
Social Networking Sites are a type of virtual community which enables many people to interact and share ideas or interests. Social networking is rapidly changing the way the world is doing virtually everything, from the way people access information to the way people communicate and most importantly, the way they interact. This study investigated the relationship between Social Networking Sites and Observational Learning of Senior Secondary School students in Mbaitoli Local Government Area, Imo State, Nigeria. Four research questions with the corresponding hypotheses were generated. The objectives of the study centered on investigating the relationship between four social networking sites namely: Facebook, Instagram, Twitter and YouTube to observational learning. The correlational study design was adopted for the study. Simple random sampling was used to draw a sample of 560 students from the population of the study. The selfdesigned instrument was of two parts: A and B. Pearson Product Moment Correlation was used to answer the research questions while the hypotheses were subjected to critical probability level of 0.05 alpha levels. Findings to this study revealed that there is a significant positive relationship between social networking sites and observational learning; some of which include enhancement of informative endowment as in the case of Facebook, live-video functionality to stories in the case of Instagram and acquisition of vocational skills from YouTube. The paper at the end recommended that more encouragement should be given to students to enable them benefit adequately and positively from the gains of social networking channels vis-a-vis observational learning.